The comparison of secondary caries between class I amalgam and class I composite restoration - Zubair, Nur Hafizah Hanem; Sukartini, Endang; Hayati, Ayu Trisna (Universitas Padjadjaran, 2010)
Introducion: Secondary caries or recurrent caries is a lesion which is observed under or around the margins or surrounding walls of an existing restoration. Amalgam has been the restorative method of choice for many years due to its low cost, easy application, strength, durability, and bacteriostatic effects. he need for restorative materials that bear similarity with natural tooth tissue such as composite resins, has increased.The aim of this study is to comparison the occurrence of secondary caries on class I amalgam and class I composite restoration. Methods: The type of research was descriptive study in which 100 samples of each class I amalgam and class I composite from department of conservative dentistry, faculty of dentistry, Rumah Sakit Gigi dan Mulut were taken. The proportion of secondary caries in both amalgam and composite restorations was analysed. Results: The result showed that the proportion of secondary caries on amalgam was 0,38 and composite was 0,19, and then was analysed with two-sample z test. There were significant differences between proportions of secondary caries on class I amalgam and the proportion of secondary caries on class I composite restorations. Conclusion: There is a difference between the proportions of secondary caries on class I amalgam and class I composite restorations where the proportion is higher in amalgam restorations compared to composite.